OPTIMALISASI PERAN KELUARGA DALAM REHABILITASI KOGNITIF DAN SPIRITUAL PENDERITA STROKE - Faizah, Imamatul; Kartini, Yanis; Sari, Ratna Yunita; Rohmawati, Riska; Hasina, Siti Nur; Aulia, Nurlisa Naila (Jurnal Pepadu, 2025)
Stroke is a major global health problem. Stroke survivors experience impairments in motor, cognitive, psychological, and sensory functions that can hinder daily activities. The independence of stroke survivors is highly dependent on family support for prolonged stroke care at home. Families and stroke survivors require education on self-management, diet, medication, and rehabilitation to prevent disability and death, thereby enhancing the meaning of life for stroke survivors. The purpose of this community service is to optimize the role of families in improving cognitive and spiritual rehabilitation for stroke survivors. The community service activities were carried out within the RW 06 area of ​​Wonokromo Village, Surabaya City. The training method used a participatory approach through lectures, discussions, brainstorming, and live demonstrations to increase family knowledge in optimizing spiritual and cognitive rehabilitation for stroke survivors. This activity was held from May to July 2025 and was attended by 56 families of stroke survivors. The results of the evaluation of the training activities showed an increase in knowledge and skills as indicated by the pretest results of 19.8% increasing to 50% of the posttest results accompanied by an increase in good skills where families can directly practice physical, spiritual and cognitive exercises that can improve neurological improvement and minimize the number of recurrent strokes.